2016
DOI: 10.1088/0957-4484/27/14/145603
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles supported on carbon nanotube carpets: influence of surface functionalization

Abstract: The effectiveness of nanoparticle-based functional devices depends strongly on the surface morphology and area of the support. An emerging powerful approach of increasing the available surface area without decreasing strength or increasing bulk is to attach arrays of suitable nanotubes on the surface, and to attach the necessary nanoparticles to them. Earlier publications by this team have shown that carpet-like arrays of carbon nanotubes (CNT) can be successfully grown on a variety of larger carbon substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Some aspects of surface wettability in these materials, and their inuence on uid-based applications have also been discussed more recently. 33,34 It was shown that CNT carpets, as fabricated, are free from detectable defects and impurities, and tend to be super-hydrophobic. They can be made permanently hydrophilic with liquid phase silica coatings and temporarily hydrophilic through microwave plasma treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects of surface wettability in these materials, and their inuence on uid-based applications have also been discussed more recently. 33,34 It was shown that CNT carpets, as fabricated, are free from detectable defects and impurities, and tend to be super-hydrophobic. They can be made permanently hydrophilic with liquid phase silica coatings and temporarily hydrophilic through microwave plasma treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The water contact angle was hardly changed before and after AgNPs modification, indicating that AgNPs modification did not affect the hydrophilicity of PEMs-SS/PVA film. Karumuri et al have reported that water contact angle has slightly gone down with AgNPs deposition, but the small difference does not affect the hydrophilicity [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Gunawan et al decorated a polyacrylonitrile (PAN) hollow fiber membrane with Ag/MWCNTs (Figure F), and the resulting membrane with well‐dispersed Ag nanoparticles (Figure G) increased the hydrophilicity of MWCNTs, yielding a huge improvement in disinfection performance . Karumuri et al concluded that surface modification approaches (oxygen‐plasma treatment and liquid‐phase silica coating) could affect the distribution, growth, and deposition densities of Ag NPs on CNTs and tune the wettability of CNTs . Reports have shown that SWCNTs exhibit antibacterial properties via direct contact with bacteria (Figure H,I) .…”
Section: Synthesis Of Antimicrobic Nanomaterialsmentioning
confidence: 99%